Representações sociais de professores sobre uma escola cívico-militar em Goiás - Queiroz, Alessandro Máximo de (2024)
This Master's Research emerges from my experiences and training based on democratic values in the personal, professional and social spheres. Since 2007, I am an effective professor linked to SEDUC-GO, currently at the Céu Azul State School, which became the Céu Azul Civic-Military State School (EECIM Céu Azul) in 2019. The research addresses the militarization of public schools, an ideological and authoritarian project of the Federal Government, which since 2019 transforms regular schools into civic-military ones. It is essential to highlight that Social Representations are constructions created by human beings to understand different realities, using behaviors, curiosities, information and the physical and intellectual domain of the world. These processes of perception of the world are social because they are based on interaction and collective sharing between what is real and what is imaginary. Representations function as support for each other and can either converge or diverge in an attempt to understand, manage or confront a given social phenomenon. Together with this aspect, the objectives of this study are to present and discuss elements that make up the semantic field of the phenomenon of social representations of civicmilitary public schools for teachers of elementary and secondary education. As an object of research, we have the Social Representations of teachers about a Civic-Military School in Goiás. This research has social relevance, entering into one of the most tense and turbulent periods in Brazil's recent history, marked by frequent threats to democracy, loss of guarantees of fundamental rights, censorship and attacks on the academic freedom. The research field of this study is the Civic-Military State School – Céu Azul, located in the municipality of Valparaíso de Goiás – GO, with elementary and high school classes both in the morning and evening. The research subjects are composed of actual teachers from the framework of the state network, coming from a public tender, and those who have employment link by temporary contract. The research is exploratory in nature and is characterized by the qualitative bias of the plurimetodological perspective, enabling the collection of data from the application of the following instruments: Technique de Association Libre de Paroles (TALP) and questionnaire. TALP aims to identify the semantic field of representations, presenting the peripheral and nuclear elements of social representation. In analyzing the data, we used the interlocution between the Theory of Social Representations and the Content Analysis proposed by Laurence Bardin, allowing us to undertake a semantic categorization of the data, resulting from the analyzes carried out based on the data obtained in TALP and the theoretical support adopted for this work. Therefore, studies like this can indicate, on the one hand, the extent to which teachers' social representations may be coordinating actions of acceptance of the use of standardization of authoritarian and coercive behaviors that exclude and deny the different identities existing in the school and, on the other hand, they reinforce and strengthen attitudes that define school as a space for the production of new knowledge.